More on the representation of contour tones - Maddieson, Ian (2024)
in LTBA IV.I Candour and Fromkin (1978, cf Candour 1975) draw attention to an alternation of tone in the Tai dialect of Lue (Li 1964) which may provide crucial evidence in favor of the representation of contour tones as indivisible units rather than as sequences of level tones. They propose that the analysis of this alternation is both simpler and more insightful if unit-contour features are posited. The advantages they claim for their solution are open to question.